تطوير مركب قائم على جسيمات نانوية من البولي فينيل كلوريد/الفضة للكشف عن الغازات - بحير الربيع; مهدية طه; ثابت سمية (جامعة الشهيد حمه لخضر بالوادي, 2025)
تُعتبر البوليمرات مواد متطورة شائعة الاستخدام، توجد تقريباً في كل مادة نستخدمها، وقد ازدادت أهميتها بشكل واضح بفضل تطبيقاتها في مختلف مجالات الصناعة. يهدف هذا العمل إلى تطوير مركب بولي فينيل كلوريد (PVC) المُدعم بجسيمات الفضة النانوية (Ag) للكشف عن الغازات. يُعد بولي فينيل كلوريد مادة بلاستيكية تتميز بتنوع خصائصها وتعدد استخداماتها، إلا أن أداءه في بعض التطبيقات يحتاج إلى تحسين. تم تحضير عينات عن طريق إدخال تراكيز وزنية مختلفة (2.5%، 5.0%، 7.5%، 10.0%) من جسيمات الفضة النانوية داخل مصفوفة (PVC) باستخدام طريقة الصب البسيطة بالمحلول في درجة حرارة الغرفة. تمر العملية بمرحلتين رئيسيتين: تطعيم أغشية (PVC) بأيونات (Ag+2)، ثم اختزالها للحصول على جسيمات الفضة النانوية في البوليمر. تم توصيف العينات باستخدام تقنيات تحليل متطورة منها: المجهر الإلكتروني الماسح (SEM) لتحليل البنية السطحية، وحيود الأشعة السينية (XRD) للكشف عن الأطوار البلورية، والتحليل الطيفي (UV-Vis) للتحقق من وجود جسيمات (Ag) داخل (PVC)، بالإضافة إلى (FTIR) لدراسة التغيرات في التركيب الكيميائي. وقد ساهمت جسيمات الفضة النانوية في تحسين خصائص الـ(PVC) بعد إضافتها للنظام. أظهرت نتائج التوصيف مدى تأثيرها الإيجابي على البنية السطحية والتركيب الكيميائي، مع خفض الشفافية وتغير اللون، مما ساهم في رفع حساسيته تجاه الغازات المستهدفة التي تم الكشف عنها بأجهزة استشعار مثل الأمونيا (NH3)، وأول أكسيد الكربون (CO)، والميثان (CH4). Polymers are advanced and widely used materials found in almost every substance we use. Their importance has grown significantly due to their applications in various industrial fields. This work aims to develop a polyvinyl chloride (PVC) composite reinforced with silver nanoparticles (Ag) for gas sensing. Polyvinyl chloride is a plastic material known for its diverse properties and numerous applications, but its performance in some applications needs improvement. Samples were prepared by incorporating different weight concentrations (2.5%, 5.0%, 7.5%, 10.0%) of silver nanoparticles into a PVC matrix using a simple solution casting method at room temperature. The process involves two main stages: doping the PVC membranes with Ag+2 ions, followed by their reduction to obtain silver nanoparticles within the polymer. The samples were characterized using advanced analytical techniques including: Scanning Electron Microscopy (SEM) to analyze the surface morphology, X-Ray Diffraction (XRD) to detect crystalline phases, UV-Vis Spectroscopy to confirm the presence of Ag nanoparticles within the PVC, in addition to FTIR to study the changes in chemical composition. The silver nanoparticles contributed to improving the properties of the PVC after their addition to the system. The characterization results showed their positive effect on the surface morphology and chemical composition, with a decrease in transparency and a change in color, which contributed to increasing their sensitivity to the targeted gases detected by sensor
Elaboration d'un Composité à base de PVC/Ag nanoparticules pour la detection des gaz
مذكرات ماستر تخصص هندسة كيميائية.2025
Keywords: المواد البوليمرية، بولي فينيل كلوريد، جسيمات الفضة النانوية، المستشعرات الغازية.; Polymeric materials; Polyvinyl chloride; Silver nanoparticles; Gas sensors